Pengaruh Marketing Mix terhadap Keputusan Nasabah dengan Kepercayaan Sebagai Variabel Intervening - Chintia Gita Sukma; Abdul Hadi; Titin Hartini (Al-Buhuts, 2023)
ABSTRACT This research begins with the question whether the marketing mix has an impact on customer decisions to use Indonesian Sharia Banks in Palembang City. The purpose of this study is to determine and assess the extent to which the marketing mix influences consumer choices. It then seeks to determine whether trust can mediate the effects of the marketing mix and sharia compliance on consumer choice. The main method of data collection is through distributing questionnaires with a Likert scale. an approach to data analysis that combines quantitative analysis with path analysis. The IBM SPSS 21 program is used by the analysis tool. The results of the study show that: 1) The marketing mix simultaneously influences customer decisions to use the services of Bank Syariah Indonesia in Palembang City, with an f count of 47.252 > 2.07 and a significance level of 0.000 0.05. Only four indicators—price, marketing, people, and physical evidence—have any real effect. 2) The marketing mix simultaneously influences trust, with a calculated f value of 58.753 > 2.07 and a significance level of 0.000 0.05. Only three variables—place, promotion, and people—have any influence. 3) The result of the t-test statistical test which has a significance value of 0.909 > 0.05 indicates that trust has no significant effect on customer decisions. 4) Marketing mix cannot be mediated by trust.